European integration and its limits: intergovernmental conflicts and their domestic origins - Finke, Daniel (ECPR Press, 2010)
Provides an empirical analysis of the three most important intergovernmental treaty conferences, showing how far voters and political parties have been able to influence treaty reforms, and examines mechanisms underlying intergovernmental negotiations in the growing European Union
references p [219]-232
Keywords: European Union -- Treaties; Europäische Union; Europe -- Economic integration; European Union countries -- Politics and government; Europäische Integration; Regierung; Mitgliedsstaaten